PENGGUNAAN INSTAGRAM @OMG.INDONESIA.ID SEBAGAI MEDIA PROMOSI UNTUK MENINGKATKAN BRAND AWARENESS PRODUK OJEK ONLINE AKU CINTA INDONESIA (ACI) DI PT BIMASAKTI MULTI SINERGI - Karunia, Kinasih Asta; Santoso , Bowo (Gapenas Publisher, 2025)
The rise of digital technology has encouraged PT Bimasakti Multi Sinergi to utilize social media as a marketing strategy for its product, Ojek Online Aku Cinta Indonesia (ACI). This study aims to enhance ACI's brand awareness through Instagram @omg.indonesia.id. The methods include problem identification through interviews and observations, promotional content creation using CapCut and Canva, and content performance evaluation based on analytics. The results indicate that promotional content successfully increased ACI's visibility and brand image through creative and consistent approaches. The study recommends increasing content variety, maximizing the use of Instagram features, and conducting regular monitoring to optimize the sustainability of marketing strategies.